2017
DOI: 10.1016/j.jcrs.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Toric outcomes: Computer-assisted registration versus intraoperative aberrometry

Abstract: Intraoperative markerless computer-assisted registration and biometric guidance summarily yielded less remaining refractive cylinder than toric IOL placement guided by intraoperative aberrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Furthermore, the postoperative median IOL misalignment was 3° at 1 day and 1 month [19], consistent with the present outcomes. A recent study shows that 28% of the mean toric IOL axis misalignment measured postoperatively is caused by intraoperative misalignment rather than postoperative rotation [20]; also, rotation between 1 hour and 1 day postoperatively was rare [20]. At 1 postoperative year, the mean toric IOL axis misalignment was 6.67°, of which 1.87° were caused by surgical misalignment and 4.80° were caused by toric IOL rotation.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the postoperative median IOL misalignment was 3° at 1 day and 1 month [19], consistent with the present outcomes. A recent study shows that 28% of the mean toric IOL axis misalignment measured postoperatively is caused by intraoperative misalignment rather than postoperative rotation [20]; also, rotation between 1 hour and 1 day postoperatively was rare [20]. At 1 postoperative year, the mean toric IOL axis misalignment was 6.67°, of which 1.87° were caused by surgical misalignment and 4.80° were caused by toric IOL rotation.…”
Section: Discussionmentioning
confidence: 98%
“…At 1 postoperative year, the mean toric IOL axis misalignment was 6.67°, of which 1.87° were caused by surgical misalignment and 4.80° were caused by toric IOL rotation. 19 Previous research suggested that a digital overlay system, including intraoperative wavefront aberrometry, and a digital marking system results in lower intraoperative misalignment and postoperative astigmatism than traditional manual marking [18,21,22]. Mayer et al found statistically signi cant differences between manual marking and digital marking with better toric IOL alignment in the digital marking group (2.0 degrees versus 3.4 degrees) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative aberrometry, allowing alignment of t-IOLs according to the overall refraction, is the latest development in alignment technology. In direct comparison, the aberrometric (Optiwave Refractive Analysis) adjustment was less accurate (remaining astigmatism 0.46 D) than the image-guided Zeiss Callisto system (residual astigmatism 0.26 D) [13]. Surgically induced transient variations of ocular refraction may have caused the relatively unfavorable outcome of the aberrometric approach.…”
Section: Meridian Of Incisionmentioning
confidence: 97%